Analisis Hasil Belajar Psikologi Mahasiswa ditinjau dari Perbedaan Kepribadian - Farihah Hesya, Aay (Ta'lim: The Islamic Religious Educational Journal, 2024)
Learning outcomes constitute one of the key indicators for measuring the effectiveness of the learning process in higher education. Among the various factors influencing the attainment of learning outcomes, personality is one of the internal variables that significantly contributes to how students comprehend and respond to academic activities. This study aims to analyze the differences in learning outcomes among psychology students in terms of extroverted and introverted personality types. The research employed a quantitative approach with a comparative design involving 100 students of the Islamic Education Study Program at STAI PUI Majalengka. The instruments used included the NEO-PI-R to assess personality traits and a learning outcomes test for the General Psychology course. The t-test results indicated significant differences between the extrovert and introvert groups, with extroverted students achieving higher average scores. These findings highlight that personality plays an important role in determining the effectiveness of student learning. The implications of this study are crucial for the development of learning strategies that are more adaptive to the diversity of student personalities.